Going public: The impact of insiders' holdings on the price of initial public offerings - McBain, Michael L.; Krause, David S. (Journal of Business Venturing, 1989)
Many entrepreneurs dream of seeing their company's securities trading in the public marketplace. Although going public has many benefits for a firm's founders and insiders, the process is often confusing and intimidating. One of the questions that investment bankers are asked frequently by insiders is, “What determines the price of a stock in the initial public offering?” This article presents empirical evidence that the stock price in an initial public offering (IPO) is directly related to the percentage of the firm's equity retained by the insiders. In other words, the offering price is relatively high when it appears that the insiders are not “bailing out” when the firm goes public. This research investigates equity ownership structure as a determinant of the pricing of IPOs. The hypothesis to be tested is: IPOs with higher (lower) insider holdings at the time of the offering are priced higher (lower) as a result of lower (higher) required rates of return. Support for the hypothesis is based on agency theory, which postulates that additional risk is created when there is a perceived separation of ownership and control. There are several implications of this research. First, a greater appreciation of the sophistication of the IPO market with regard to the actions of the insiders should be gained. Second, the reader's knowledge of the activity and relative pricing of IPOs during the 1978–1985 time period should be enhanced. Third, insiders should realize that actions regarding their relative equity holdings at the time of the offering have an impact on the price of the offering. Finally, the reader should recognize that even in “hot markets” the actions of insiders at the time of an initial public offering regarding the sale of equity are monitored by the market.